A 3D geological model of the horn of Africa: New insights for hydrogeological simulations of deep groundwater systems - Quiroga, E; Bertoni, C; van Goethem, M; Blazevic, LA; Ruden, F (Elsevier, 2022)
Study Region: The area of interest comprises 1.6 million km² of the Horn of Africa, extending 60 km offshore the Gulf of Aden and Indian Ocean, and delimited by the Tana River in Kenya and the Rift Valley in Ethiopia. Study Focus: Deep (> 400 m) groundwater resources are virtually unexplored in the Horn of Africa. One of the main challenges in this vast and sparsely documented area, is producing solid geological models. This paper presents a first-order assessment of the deep structure and water resources in the region, based on the integration of data from hydrogeological and Oil & Gas exploration. Public domain cross-sections, geological maps, and satellite data are reinterpreted, defining the extent of formations in the subsurface. The data integration benefits from using a multi-source modelling platform, subsurface mapping software from the Oil & Gas and hydrogeology sectors, and proprietary scripts. New Hydrological Insights: The present study reveals new evidence of the presence of deep aquifer systems in the Horn of Africa. The model outputs include the extent, predicted thickness, salinity, and petrophysical properties of the potential aquifers. The results of this first extensive 3D subsurface model for the region provide new hydrogeological insights into potential transboundary aquifers and can be used as a baseline for further investigations and, ultimately, for quantifying the total water resources in the region.